Способ иммобилизации радиоактивных отходов в минералоподобной матрице - Аншиц А. Г. Александр Георгиевич; Верещагина Т. А. Татьяна Александровна; Васильева Н. Г. Наталия Геннадьевна; Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Бондин В. В. Владимир Викторович; Кривицкий Ю. Г. Юрий Григорьевич; Крючек Д. М. Дмитрий Михайлович; Смирнов С. И. Сергей Иванович
опубл. 10.01.12